Prevalence and associated factors of pre-eclampsia among pregnant women attending anti-natal care at Mettu Karl referal hospital, Ethiopia: cross-sectional study - Alemayehu Sayih Belay; Tofik Wudad (BMC, 2019)
Abstract Background Preeclampsia is leading causes of maternal and perinatal morbidity and mortality worldwide and it is a hypertensive disorder which usually occurs after 20 weeks of gestation. In Ethiopia, according to Ethiopian National Emergency Obstetric and Newborn Care about 10% of all maternal mortality (direct and indirect) were due to preeclampsia. Despite this condition has adverse effects on the maternal and child health, its prevalence is still significant especially in developing countries including Ethiopia. Objectives The aim of the study is to assess the prevalence and associated factors of preeclampsia among pregnant women attending antenatal care at Mettu Karl referral hospital. Method The study was conducted at Mettu Karl referral hospital using institutional based cross sectional study design among women whose age was greater or equal to eighteen from March to April 2018. Data were collected from 129 participants by face to face interview technique using structured and pretested questionnaire. Logistic regression analysis was used to identify the factors associated with preeclampsia development. Result A total of 129 participants were enrolled in the study with the mean age of 25.87 [SD ± 4.757]. Prevalence of preeclampsia among the current pregnant women who attend ANC in Mettu Karl Hospital were 16 (12.4%) with 95% CI (7, 18). Predictor variables like respondents age (AOR = .009, 95% CI = [.000, .317]), current multiple pregnancy (AOR = .071, 95% CI = [.007, .773]) and history of diabetes mellitus (AOR = .058, 95% CI = [.007-.465]) were significantly associated with the current preeclampsia. Conclusion The finding of this study showed that a considerable proportion of women had preeclampsia. Health seeking behavior towards pregnant women's should be encouraged for both urban and rural residents, which provide a chance to diagnose preeclampsia as early as possible and to prevent the coming complication towards preeclampsia.